Revisión N-3 fatty acids in glucose metabolism and insulin sensitivity - Santa Olalla, L. M. de; Sánchez-Muniz, F. J.; Vaquero, M. Pilar (Aula Médica Ediciones, 2009)
Polyunsaturated fatty acids (PUFA) of the n-3 series are essential for normal growth and development. The health effects of these fatty acids include reduction of cardiovascular risk due to antiarrhythmic, antiinflammatory, anti-thrombotic and lipid lowering actions. An increase in unsaturation of the muscle membrane fatty acids is associated with improved insulin sensitivity. Higher proportion of n-3 fatty acids may have beneficial roles, such as antiobesity effects and protection against the metabolic syndrome and type 2 diabetes mellitus through a number of metabolic effects. However, controversy exists on the different effects of n-6 and n-3 polyunsaturated fatty acids as well as on the interacting effect of dietary saturated and monounsaturated fat. In addition, some adverse effects have been described concerning the use of fish oil supplements containing high doses of n-3 fatty acids. Several studies show Eskimos diabetes risk, while results of nutritional interventions on the influence of consuming diets rich in oily fish or other food rich in n- 3 fatty acids is very limited. This article reviews the possible mechanisms through which n-3 PUFA are involved in glucose level control and insulin sensitivity. Intervention and epidemiological studies together with recent findings on the nutrigenomic field related with this subject are also briefly reviewed. Peer Reviewed